A focus on selected perspectives of the NUMEN project. Issue 1 (1st September 2022) - Cavallaro, M.; Agodi, C.; Bellone, J.I.; Brasolin, S.; Brischetto, G.A.; Bussa, M.P.; Calabrese, S.; Calvo, D.; Campajola, L.; Capirossi, V.; Cappuzzello, F.; Carbone, D.; et al.
Abstract: The use of double charge exchange reactions is discussed in view of their application to extract information that may be helpful to determinate the nuclear matrix elements entering in the expression of neutrinoless double beta decay half-life. The strategy adopted in the experimental campaigns performed at INFN - Laboratori Nazionali del Sud and in the analysis methods within the NUMEN project is briefly described, emphasizing the advantages of the multi-channel approach to nuclear reaction data analysis. An overview on the research and development activities on the MAGNEX magnetic spectrometer is also given, with a focus on the chosen technological solutions for the focal plane detector which will guarantee the performances at high-rate conditions.